Investments of small and medium enterprises and their effects on economic growth: A standard analytical study of Algeria’s condition during the period 2000-2021 - Adda, Mohammed Cherif; Abdelkader, Kadid (International journal of economic perspectives, 2025)
The purpose of this study is to addresse the investments of small and medium enterprises represented by both imports and exports, and the value of investment and chowing their effects on economic growth in Algeria, as well as the effort made by the state to encourage these institution during the period (2000-2021). The study concluded that there is an inverse relationship between the imports of small and medium enterprises and economic growth, while there is a significant direct relationship statistical, between the economic growth of Algeria, and the exports and investments of these institutions outside the fuel sector, and this according to the outputs of the (eviews10)